The Impact of Macroeconomic Variables on Stock Market Performance: Evidence on the Mediating Role of Monetary Policy from Indonesia - Marco Hadi Surya; Hartono (Universitas Kadiri, 2025)
This study investigates the complex relationship between macroeconomics and the Indonesian stock market, focusing on the often-overlooked mediating role of monetary policy. Employing path analysis on quarterly data from 2005-2024, the study models the direct and indirect effects of inflation, GDP, and unemployment on the Composite Stock Price Index (IHSG) via the BI rate. Results show that unemployment and the BI rate have a direct, significant negative impact on the IHSG. Crucially, the findings reveal that inflation's impact is fully mediated by the interest rate, clarifying previous inconsistencies in the literature. This analysis confirms the significance of the asset price channel of monetary policy transmission in Indonesia.